High School Career Technical Education and New Mathematics Graduation Pathways - Stevens, Rachel (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2020)
Career Technical students in Ohio now have lowered graduation requirements. This has led to many questions about how this change can still create a worthwhile education. Teachers in Ohio Career Tech are worried that lowering the content expectations will lower students’ ability to reason mathematically. Data collected leads to the conclusion there is no statistically significant relationship between level of courses taken in high school and mathematical reasoning. Therefore, lowered math course requirements do not hinder students’ growth but instead open the door for new approaches to math education. New approaches and new curriculum may improve students’ overall understanding. The Career Technical Education graduation requirements for mathematics should be individualized based on each student’s intended career.